Analisis Penanggulangan Kadar Gas H2S Pada Aliran Minyak Di Stripper Melalui Penerapan Injeksi Sweetening Gas dan Oil Rate - Lilo Al Fiqriansyah; Abror, Hadziqul; Triono, Agus (Journal of Sustainable Energy Development, 2024)
This research evaluates the performance of an existing stripper in handling H2S content in the oil stream in Sukowati Field, Bojonegoro Regency. With H2S content ranging from 2-3%, there's a risk of danger and damage to the piping system. The study aims to assess the stripper's performance, propose an optimization scenario for managing H2S content, and compare the existing stripper's performance with the optimization scenario. The research involved evaluating the stripper from October to December 2023, formulating an optimization scenario, and implementing it in January 2024. Results indicate that the % absorption ratio in the sweetening process averaged 98.99% in the existing stripper and 99.75% in the optimization scenario. The oil rate to sweetening gas ratio averaged 89.31% in the existing stripper and 88.01% in the optimization scenario. The sweetening gas injection to oil rate ratio averaged 10.7% in the existing stripper and 12.0% in the optimization scenario. The optimization scenario reduced H2S content from 24000 ppm to 60 ppm, meeting standards. Overall, optimizing the oil rate to sweetening gas injection ratio improved H2S content reduction efficiency in the stripper, with H2S content at the outlet less than 100 ppm.